CONSTITUTIONAL ANOMALIES IN CHILDREN: FEATURES OF THE COURSE OF EXUDATIVE CATARRHAL DIATHESIS IN CHILDREN - Oxundadayeva Muxayyo Musinovna (Modern American Journals, 2025)
Exudative catarrhal diathesis (ECD) is one of the most common manifestations of constitutional anomalies in early childhood. This article explores the clinical features, progression, and diagnostic challenges of ECD in children with constitutional predispositions. Based on a review of clinical cases and recent studies, the paper identifies the typical symptoms such as persistent allergic reactions, skin rashes, and frequent upper respiratory tract infections. Particular attention is given to the role of genetic, immunological, and environmental factors in the development of ECD. The study emphasizes the importance of early diagnosis and individualized treatment approaches to mitigate complications and support healthy development. A multidisciplinary strategy involving pediatricians, allergists, and nutritionists is recommended for effective management.
Keywords: Exudative catarrhal diathesis, Constitutional anomalies, Pediatric dermatology, Allergic reactions, Immune response in children, Early childhood disorders, Genetic predisposition, Multidisciplinary treatment.